Sexual Harassment in Academia: Analysis of Opinion Articles in the Portuguese Press - Maria João Faustino; Isabel Ventura; Maria Helena Santos; Júlia Garraio; Carla Cerqueira (Journalism and Media)
#MeToo furthered the debates about sexual harassment in academia in different contexts and locations. In Portugal, two moments drove the media debates around sexual harassment in higher education. Specifically, the allegations that emerged at the Faculty of Law of the University of Lisbon (FDUL) in 2022, and the case related to the Centre for Social Studies (CES) of the University of Coimbra in 2023. This study aimed to investigate the media coverage of these cases and their respective contributions to the national debate on sexual harassment in academia. We analysed the opinion articles published online between April 2022 and June 2023 in five Portuguese newspapers, Diário de Notícias, Jornal de Notícias, Público, Expresso, Observador, and Correio da Manhã, conducting a comparative analysis of the two cases. Sexual harassment was broadly discussed as an endemic reality, exacerbated by the precariousness and gendered hierarchical structures of academia. At the same time, there was a tendency to personalize the debate, by focusing on Boaventura Sousa Santos, CES’s emeritus director. This served as a basis for the instrumentalization of sexual violence as a form of political attack against the left, thus weakening the potential of the debates about sexual and moral harassment in academia.